A study on the effects of arsenic toxicity on oviduct histomorphology in the female rat. (2nd October 2018) - Akram, Zertashia; Jalali, Samina; Kalsoom, Ommia; Batool, Sajida; Shami, Sajjad Aslam
ABSTRACT: Arsenic-contaminated drinking water and its association to different diseases has been considered a severe problem worldwide. The goal of the present study was to evaluate the histopathological changes in oviduct of female rat following 4-week exposure to different doses (50, 100, and 200 ppm) of sodium arsenite. Treatment was initiated when rat reaches the age of 4 weeks. Body weight of animals was recorded weekly. Weight, diameter, and arsenic deposition in oviduct were estimated. Based on anatomical division of oviduct, histology of isthmus and ampulla was examined for any histopathological changes. A dose-dependent decrease was observed in body weight and oviduct weight of treated rats as compared to untreated control rat and low-dose group. Higher arsenic deposition was found in oviduct with the increased doses of arsenite. Cellular arrangement was found disorganized and loosely packed in the epithelium and muscle layers of all treated groups, but was more conspicuous at 200 ppm dosage. Fewer cilia were seen in isthmus and ampulla of treated groups, and almost no cilia were observed in isthmus of 200 ppm group. Muscle layer thickness and epithelium height of arsenic treated rats was reduced in a dose-dependent manner from low (50 ppm) to high group (200 ppm) as compared to control rats. This study found that arsenite treatment adversely affected the body weight of female rats and induced histopathological changes in the cellular structure, configuration, and organization of oviduct in female rats.